Degradable thermoresponsive core cross-linked micelles fabrication, surface functionalization, and biorecognition - Jiang, Xiaoze (Langmuir : the ACS journal of surfaces and colloids, 2009)
We report on the fabrication of core cross-linked (CCL) micelles possessing thermoresponsive and degradable cores and biocompatible coronas cofunctionalized with carbohydrate and biotin moieties. Well-defined poly(2-aminoethylmethacrylamide) (PAEMA) homopolymer was first synthesized in a controlled fashion via the reversible addition-fragmentation chain transfer (RAFT) process. CCL micelles comprising of well-solvated PAEMA coronas and thermoresponsive cores were then obtained in a one-pot manner via RAFT copolymerization of N-isopropylacrylamide (NIPAM) and bis(2-methacryloyloxyethyl) disulfide (DSDMA) difunctional monomers by employing PAEMA as the macro-RAFT agent. In the presence of dithiothreitol (DTT), the obtained CCL micelles can be disintegrated into unimers due to the cleavage of disulfide cross-linkers, whereas deswelling of micellar cores can be achieved via heating above the phase transition temperature of PNIPAM. Thus, the release profiles of this type of nanocarriers are expected to be triggered by temperature and thiols or a combination of both. Furthermore, primary amine residues located within coronas of CCL micelles have been further exploited for surface functionalization with biotin and carbohydrate moieties, rendering them biocompatible and bioactive. The availability of biotin within the coronas of CCL micelles was confirmed by HABA/avidin binding assay and Diffractive Optics Technology (DOT) biosensing instrument. After the micelles were immobilized on the surface of avidin-sensor chip, specific biorecognition of the available biotins and carbohydrate moieties on the CCL micelles was further confirmed. We expect that this novel type of bioactive and potentially biocompatible CCL micelles can be employed as smart nanocarriers for targeted drug delivery and controlled release